Multisystem inflammatory syndrome in children (MIS-C) and the coronavirus pandemic: Current knowledge and implications for public health - Megan S. Rafferty; Hannah Burrows; Jake P. Joseph; Jennifer Leveille; Snejana Nihtianova; E. Susan Amirian (Elsevier, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has caused widespread mortality and morbidity. Though children are largely spared from severe illness, a novel childhood hyperinflammatory syndrome presumed to be associated with and subsequent to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has emerged with potentially severe outcomes. Multisystem inflammatory disorder in children (MIS-C) most commonly affects young, school-aged children and is characterized by persistent fever, systemic hyperinflammation, and multisystem organ dysfunction. While uncommon and generally treatable, MIS-C presents potentially life-altering medical sequelae, complicated by a dearth of information regarding its etiology, pathophysiology, and long-term outcomes. The severity of MIS-C may warrant the need for increased awareness and continued COVID-19 mitigation efforts, particularly until potential factors conferring a predisposition to MIS-C can be clarified through additional research. Well-informed guidelines will be critical as the school year progresses. In this article, current knowledge on MIS-C is reviewed and the potential implications of this novel syndrome are discussed from a public health perspective.